Monitoring Next Cloud sebagai Private Cloud Storage dengan Notifikasi Telegram - Novita Sari; Hidra Amnur; Rahmat Hidayat (SOTVI - Society of Visual Informatics, 2020)
Online Storage such as Cloud Computing is the platform most widely used as an online storage that can be accessed anywhere and anytime. Currently Cloud Computing is experiencing development. One of them is providing media storage that users can use and save data safely. Nextcloud is Open Source that provides storage service. Nextcloud is free amd open source storage service that includes security/privacy and monitoring features. Cloud Monitoring information delivered by Telegram Bot. Telegram users can communicate with Telegram Bot to get monitoring information about Nextcloud. There are several commands that are used to obtain monitoring information